The effectiveness of outdoor recreation programs in fostering interpersonal communication skills and group cohesiveness / Muhammad Irfan Azhari ... [et al.] - Azhari, Muhammad Irfan; Md Yusof, Mohd Khairulanwar; Mohd Aznan, Ellail Ain; Mohd Yazid, Siti Amalina (Universiti Teknologi MARA, Perlis, 2025)
Outdoor recreation programs are designed to promote leisure and physical activity while fostering stronger social connections among people. People often face various difficulties in communication due to a combination of environmental factors. Some common challenges and difficulties among students in their communication include measurement and conceptualization of group effectiveness. Therefore, the study aims to examine the effectiveness of outdoor recreation programs towards interpersonal communication skills and group cohesiveness among Universiti Teknologi MARA Campus Seremban. The research instrument used was the Interpersonal Communication Scale (ICS) and the Group Environment Questionnaire (GEQ). A total of 118 students who take part in outdoor recreation programs were chosen as participants consisting of 59 males and 59 females. For interpersonal communication, the highest mean score was ‘External Perception’ (M = 4.92) and for group cohesion, the highest mean score was ‘Group Integration Task’ (M =5.59). The results indicate that there were no significant differences spotted in interpersonal communication and group cohesion that influence participants when participating in outdoor recreation programs between genders among respondents. This study indicates that such programs are equally beneficial for both male and female students in improving their ability to communicate and interact with others. This insight can be used to promote gender-neutral approaches in designing and implementing these programs, ensuring equal opportunities for all participants. This study can provide the FSR UiTM Seremban with general information on the effectiveness of outdoor recreation programs for their students.